Mortality trends of liver diseases in mainland China over three decades: an age-period-cohort analysis - Chaojie Liu; Yang Sun; Jie Chang (BMJ Open)
Objective To analyse mortality trends of liver diseases in China over the past 30 years.Design Age-period-cohort analyses were applied to liver diseases data obtained from the Chinese Health Statistics Annual Report (1987–2001) and the Chinese Health Statistics Yearbook (2003–2017).Setting General population in mainland China.Outcomes Mortality rates and age, period and cohort effects on three categories of liver diseases: primary liver cancer (PLC), chronic liver disease and cirrhosis (CLD), and viral hepatitis (VH).Results A total of 13.54 million deaths were attributable to liver diseases over the period between 1987 and 2016, resulting in an average of 36.15 deaths per 100 000 population per year. The risk of PLC mortality increased by 32.69% over the period after controlling for the effects of age and birth cohort. By contrast, the risk of CLD mortality decreased by 56.64% over the same period. The risk of VH mortality decreased first, followed by a resurgence after the period of 2002–2006. Similar mortality risk trends by age (increasing) and birth cohort (decreasing) were observed for PLC and CLD. The year 1952 represented a turning point for VH, with people born after 1950 experiencing a declining risk of VH mortality.Conclusions China has achieved great success in reducing the mortality of VH and CLD. However, significant challenges lie ahead in the efforts to prevent and control PLC and the resurgence of VH.